Long non-coding RNA metallothionein 1 pseudogene 3 promotes p2y12 expression by sponging miR-126 to activate platelet in diabetic animal model. (19th May 2019) - Zhou, Ming; Gao, Meng; Luo, Yanwei; Gui, Rong; Ji, Hongwen
Abstract: Platelet hyperaggregation and hypercoagulation are associated with increase of thrombogenic risk, especially in patients with type 2 diabetes (T2D). High activity of P2Y12 receptor is found in T2D patients, exposing such patients to a prothrombotic condition. P2Y12 is a promising target for antiplatelet, but due to P2Y12 receptor constitutive activation, the clinical practical phenomena such as "clopidogrel resistance" are commonly occurring. In this study, we investigate the role of lncRNA on platelet activation. By lncRNA array, we screened thousands of differentially expressed lncRNA in megakaryocytes from T2D patients and confirmed that lncRNA metallothionein 1 pseudogene 3 (MT1P3) was significantly upregulated in megakaryocytes from T2D patients than in healthy controls. And we further investigate the biofunction of MT1P3 on platelet activation and the regulatory mechanism on p2y12. MT1P3 was positively correlated with p2y12 mRNA levels and promoted p2y12 expression by sponging miR-126. Knockdown of MT1P3 by siRNA reduced p2y12 expression, inhibiting platelet activation and aggregation in diabetes animal model. In conclusion, our findings identify MT1P3 as a key regulator in platelet activation by increasing p2y12 expression through sponging miR-126 under T2D condition. These findings may provide a new insight for managing platelet hyperactivity-related diseases.